Impact of CSR Practices on Firms’ Goodwill: An Empirical Investigation - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana (Integrated Journal for Research in Arts and Humanities, 2022)
Corporate Governance is the administration of a corporation following legal, ethical, financial, and cultural considerations in the most optimal manner. The organization's middle-of-the-road respect for consumers, employees, partners, and the environment. This review evaluates the significance of communicating the CSR initiatives of institutions to companions. The study reveals that corporations must articulate their CSR initiatives with precision and resolve to gain their partners' generosity. A portion of the channels for delivering CSR campaigns includes credible announcements, internal web interfaces, bulletins, messages, TV advertisements, print ads, board notices, and Internet correspondences, which provide opportunities to attract and share information with vast audiences. As a result, the study demonstrates that each organization must communicate its corporate social responsibility initiatives to its partners via several communication channels, as this is one way of eliciting the generosity of its partners. The current research is descriptive and contacted 160 respondents. For data analysis, the Mean and t-test were used.